Application of Cooperative Learning Model Type Teams Games Tournament (TGT) with Demonstration Based to Improve the Learning Outcomes of Colloid Topic in Student Class XI SMA Negeri 7 Palu - Nur Intan; Minarni R. Jura; Ijirana Ijirana (Jurnal Akademika Kimia, 2019)
This study aimed to obtain a description of implementation on student’s learning outcomes the application of cooperative learning model of TGT based on demonstration Class XI on colloid material in SMA Negeri 7 Palu. The type of research used in this research was pre-experimental designs (non-designs) with research design that was one-group pre-test post-test design. Sampling in this study was chosen by purposive sampling. The sample consisted of two classes, class XI IPA 1 as experimental class 1 (n = 28) and class XI IPA 2 as experiment class 2 (n = 29). Student learning outcomes were processed using inferential statistical analysis of the Wilcoxon Rank-Unparpulated Ranking nonparametric test. The results showed that the experimental class 1 was Zcount (-4.62) <Ztable (-1.96) and experiment 2 was Zcount (-4.70) <Ztable (-1.96). The effectiveness of the implementation of learning model of TGT based on demonstration to words student learning outcomes can also be seen from the assessment of student learning outcomes with the average posttest score for experimental class 1 was 83.29 and experiment class 2 was 80.86 with the result of N-gain calculation for both experiment class included in high category that was equal to 0.83 and 0.85. So it can be concluded that the implementation of learning model of TGT based on demonstration can improve student learning outcomes with average greater than 75 on colloid material in SMA 7 Palu.